2020
DOI: 10.3171/2019.8.spine19201
|View full text |Cite
|
Sign up to set email alerts
|

A combination of mesenchymal stem cells and scaffolds promotes motor functional recovery in spinal cord injury: a systematic review and meta-analysis

Abstract: OBJECTIVEThere is controversy about the role of scaffolds as an adjunctive therapy to mesenchymal stem cell (MSC) transplantation in spinal cord injury (SCI). Thus, the authors aimed to design a meta-analysis on preclinical evidence to evaluate the effectiveness of combination therapy of scaffold + MSC transplantation in comparison with scaffolds alone and MSCs alone in improving motor dysfunction in SCI.METHODS Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 55 publications
3
21
0
Order By: Relevance
“…After SCI was induced, the protocol required the injection of biomaterials (made of diblock copolypeptide hydrogels) delivering fibroblast growth factor 2, EGF, glial cell-derived neurotrophic factor (GDNF), and integrin-blocking antibody [ 170 ]. Other than compounds, bio-scaffolds can also in this case be used to deliver stem cells, most frequently human mesenchymal stem cells, widely used in the treatment of the disease [ 269 , 270 , 271 ], but scaffolds complexed with NPCs have also been developed [ 166 , 272 , 273 ]. It is worth mentioning that in the case of SCI, biomaterials (in particular the Neuro-Spinal Scaffold - InVivo Therapeutics Corp.) have also been used in clinical practice [ 167 , 168 ].…”
Section: The Role Of Scaffolds In Developing Regenerative Therapiementioning
confidence: 99%
“…After SCI was induced, the protocol required the injection of biomaterials (made of diblock copolypeptide hydrogels) delivering fibroblast growth factor 2, EGF, glial cell-derived neurotrophic factor (GDNF), and integrin-blocking antibody [ 170 ]. Other than compounds, bio-scaffolds can also in this case be used to deliver stem cells, most frequently human mesenchymal stem cells, widely used in the treatment of the disease [ 269 , 270 , 271 ], but scaffolds complexed with NPCs have also been developed [ 166 , 272 , 273 ]. It is worth mentioning that in the case of SCI, biomaterials (in particular the Neuro-Spinal Scaffold - InVivo Therapeutics Corp.) have also been used in clinical practice [ 167 , 168 ].…”
Section: The Role Of Scaffolds In Developing Regenerative Therapiementioning
confidence: 99%
“…[ 175–179 ] Furthermore, it was demonstrated that MSCs seeded in different scaffolds transplanted into injured spinal cord facilitate post‐traumatic regeneration of nervous tissue to a greater extent than MSCs infused as a cell suspension. [ 180–182 ]…”
Section: Experimental Attempts To Use Mesenchymal Stem Cells In the Tmentioning
confidence: 99%
“…Furthermore, the scaffold itself also has the function of inhibiting glial scar formation, subside inflammation, stimulate angiogenesis and promote neurogenesis [ 94 , 97 ]. The systematic review and meta-analysis conducted by Yousefifard et al [ 98 ] showed that combination of MSCs and scaffolds is more effective compared to MSCs and scaffolds alone in improving the motor function in animal SCI models.…”
Section: Novel Biological Therapies For Spinal Cord Injurymentioning
confidence: 99%